ELUCIDATION ON THE EFFECT OF OPERATING TEMPERATURE TO THE TRANSPORT PROPERTIES OF MEMBRANES USING MOLECULAR SIMULATION TOOL - MASH’AL, AL-AMEERAH (IRC, 2017)
Annually, a huge amount of natural gas has been extracted for daily usage in the whole world. Before supplying to users all over the world, the natural gas has to be treated prior to entering the pipeline. Aside from using amine absorption technology, membrane technology has risen up and been demanded in many oil and gas company as it is more efficient in treating a high concentration of impurities in natural gas. The issue of temperature dependent phenomena onto the membrane remains unclear. Existing reports in the affected performance and selectivity of membrane are in a small number. A sequence of molecular membrane was designed and simulated to see the effects of different operating temperature onto its structure and transport properties. This study was performed by Materials Studio Software by using a force field function for system configurations that are reliable and consistent. The simulation model has been validated with experimental data with a satisfactory agreement. The simulations tested on the membrane showed that with an increasing temperature, it has affected the solubility, diffusivity and permeability of the polymer. Solubility has shown a decrement in value when increased in temperature, but it is opposite to diffusivity where the value is increasing as the temperature increasing. For the permeability, the value is governed by the solubility coefficient as it has more dominance over diffusivity coefficient. Hence, the permeability decreases as the temperature increases. This simulated method has a higher potential to be used in oil and gas industries where impurities from natural gas or oil is to be separated via membrane separation and at the same time saving a lot of time and cost.